Dampak Kebijakan Spin-off Terhadap Kinerja Bank Syariah - Nasuha, Amalia (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2012)
The purpose of this study is to discover differentiation financialperformance of five sharia banks in Indonesia (BNI Syariah, BRI Syariah, BJB Syariah, Bank Syariah Bukopin, and Bank Victoria Syariah) one year before spin-off activity and one year after spin-off activity. The method used in this research is Wilcoxon Match Pairs Test with nine variables, which are asset, financing, third party funds, net incomes, dan five ratios: CAR, NPF, FDR, ROA, and ROE. The result of this study are, four variables indicate that there are differences in financial performance. Therefore, sharia business units should prepare themself before clause of spin-off in 2023DOI: 10.15408/aiq.v4i2.2534